2017
DOI: 10.1155/2017/7967380
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cholesterol, Triglycerides, Calculated, and Measured Lipoproteins: Whether Calculated Small Density Lipoprotein Fraction Predicts Cardiovascular Risks

Abstract: Background Recent literature in lipidology has identified LDL-fractions to be more atherogenic. In this regard, small density LDL-cholesterol (sdLDLc) has been considered to possess more atherogenicity than other LDL-fractions like large buoyant LDL-cholesterol (lbLDLc). Recently, Srisawasdi et al. have developed a method for calculating sdLDLc and lbLDLc based upon a regression equation. Using that in developing world may provide us with a valuable tool for ASCVD risk prediction. Objective (1) To correlate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The training dataset will be used to construct the model, while the validation dataset will be used to verify it. The Waist, HDL, and blood pressure status all have a significant effect on triglycerides, according to a multilayer perceptron analysis, and these results are in line with the recent study done on elderly Japanese men [ 14 ], concluding that triglycerides are positively associated with blood pressure and with hypertension [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…The training dataset will be used to construct the model, while the validation dataset will be used to verify it. The Waist, HDL, and blood pressure status all have a significant effect on triglycerides, according to a multilayer perceptron analysis, and these results are in line with the recent study done on elderly Japanese men [ 14 ], concluding that triglycerides are positively associated with blood pressure and with hypertension [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, the pathogenesis of MetS remains unclear, and several other components have been shown to have higher sensitivity and specificity for predicting MetS [27,64]. Nonetheless, the harmonised definition seems to have left out some important adjustments to the variables that report on each MetS component such as the waist-to-height ratio [64], waistto-hip ratio [65], mean arterial pressure [66] and LDL levels [67], all of which have been reported as better screening criteria for MetS. BMI has been previously considered in AACE and IDF definitions and retains its usefulness as an alternative parameter for the assessment of central obesity [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was limited for the T2DM subjects with normal lipid profile, within normal ranges, we observed the same pattern of changes in lipid profile parameters as it can be observed in diabetic dyslipidemia, which is associated with high levels of TG, total cholesterol, LDL and low levels of HDL along with predominant sdLDL-C 13,14 . High levels of sdLDL-C in T2DM is a major complication of diabetes that can induce atherosclerosis in diabetic patients 6,15,16 . In the present study, high sdLDL-C levels indicate that T2DM patients may have atherogenic risk despite the lipid profile within a normal range.…”
Section: Discussionmentioning
confidence: 99%
“…SdLDL also induces thickness in intima-media of blood vessels and numbers of sdLDL particles are associated with insulin resistance in T2DM 22 . Glycation rates are associated with increased atherosclerosis, morbidity and mortality in cardiovascular diseases (CVD) 6 . In this regard, our study (which did not include any dyslipidemic patient) demonstrated that there is a strong positive correlation between glycemic status and sdLDL-C in T2DM patients that may contribute for the induction of atherosclerosis and may lead towards CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation